Migração nordestina para o corte de cana no Mato Grosso: “Porque eu vim moça, eu vou lhe contá” - Costa, Regina Maria da (2010)
The background of the flux migratory movement to the Mato Grosso State, as in the hole Brazilian territory, characterized by the absence of Agrarian Reform applicability, this absence make the production impossible in many regions, such as the Northeast, which directly contributes to the migratory rate increase. To have land and having not condition to expand production, or yet, to transport it competitively, it is the same that not to have. The migrants production in their land is usually for subsistence and when they need the resource to suply their needs, for example, the purchase of a property, the effectuation of improvements in their living environment or even in cases of health is a major challenge because the resources are insufficient. The purpose of this dissertation is to investigate the motivations that lead northeastern workers to the sugar cane cut job in the Mato Grosso state. To meet this goal, we adopted the research methodologies: qualitative and life history, which allowed the use of essential tools, such as observation and interviews (informal and recorded) by the which was possible to record the main motivations of migrants in the sugarcane activities in the Barrálcool plant in Barra do Bugres. This scenery showed that migrants feel encouraged by the region of Mato Grosso State for the following reasons: A) to have the opportunity in the sugar cane cut job to those that have not experience yet, situation known by the cutters as white paper, B) by the believe that the work in the plant of the Mato Grosso State offers better conditions in relation to remuneration than in other states, C) the possibility of receiving insurance in alternating seasons and D) despite Barra Bugres town be relatively little compared to other towns, it offers the chance of fixing housing in neighborhoods and settlements, and even this is not the focus of this study, we identified the presence of some established families, and finally, E) we also found that for some migrants, the work in the plants has offered ways to the realization of dreams, as the acquisition of goods and investments in construction of accommodation to house new migrants wish to come to the Mato Grosso. Still arises the proposal of a category of migrants who are uncertain/imprecise, where the return displacement to the origin location is defined by the remuneration factor.